Policing reform: a historical and contemporary analysis - Barker, Thomas (Cognella, 2024)
Policing Reform: A Historical and Contemporary Analysis provides readers with an in-depth analysis of the past, present, and future of modern American policing. The opening chapter explores social control and the seeds of modern policing, foundations of law enforcement in the U.S., and policing in the early United States. Additional chapters examine the role of American police, the legacy of bigotry within the vocation, and the characteristics of policing as a profession. Students learn about community policing as a possibility for American police reform, problem-oriented policing, and procedural justice and police legitimacy. The book addresses police crime as occupational deviance, excessive use of force, criminal police, police accountability, and police accreditation. The closing chapter addresses the American national police crisis and possible solutions for police reform, including accountability-based policing. Each chapter features chapter objectives, an introduction, questions for discussion, and key terms to support the student learning experience. Providing students with a holistic view of the policing profession and a solutions-focused approach, Policing Reform is a timely and essential resource for courses and programs in policing, law enforcement, and criminal justice.--back cover